Petrography and geochemistry of the impact to postimpact transition layer at the El'gygytgyn impact structure in Chukotka, Arctic Russia - Karin Maierhofer (Department of Lithospheric Research, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Christian Koeberl (Department of Lithospheric Research, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Julie Brigham‐Grette (Department of Geosciences, University of Massachusetts) (Meteoritics & Planetary Science, 2019)
The abstract is available here: https://uscholar.univie.ac.at/o:1095794 The abstract is available here: https://uscholar.univie.ac.at/o:1095794